Nanoscale lithium battery separator coating suitable for electrohydrodynamic EHD jet printing technology

By developing nano-grade lithium battery separator coatings suitable for electro-hydrodynamic EHD jet printing technology, the problem of difficult to achieve uniform bonding and uniform ionic conductivity in the prior art is solved, which significantly improves the cycle life of lithium batteries and reduces production costs.

CN114464957BActive Publication Date: 2025-03-25NINGDE ZHUOGAO NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210128971.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-11
Publication Date
2025-03-25
Estimated Expiration
2042-02-11

AI Technical Summary

Technical Problem

The existing lithium battery separator coatings are difficult to achieve uniform bonding and uniform ionic conduction in electro-hydrodynamic EHD jet printing technology, resulting in insufficient battery cycle life.

Method used

A nano-grade lithium battery separator coating suitable for electrohydrodynamic EHD jet printing technology was developed. By rationally preparing the emulsion, polymethyl methacrylate, emulsifier BYK-LPX 20990, thickener CMC, binder acrylic resin and conductivity regulator ethanol were added to form a stable suspended emulsion to ensure that the emulsion does not decompose at high voltage and achieve uniform point coating.

Benefits of technology

This coating realizes uniform bonding between the separator and the positive and negative electrodes in electro-hydraulic dynamic jet printing technology, provides uniform ionic conduction, significantly improves the cycle life of high-energy density batteries, and reduces the amount of adhesives, saving production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114464957B_ABST
    Figure CN114464957B_ABST
Patent Text Reader

Abstract

The invention discloses a nanoscale lithium battery diaphragm coating suitable for electro-hydraulic dynamics jet printing technology, comprising the following components by weight percentage: polyvinylidene fluoride-hexafluoropropylene copolymer resin PVDF-HFP (5-20)%; emulsifier (1-4)%; auxiliary agent (0.05-5)%; conductivity regulator (0.5-8)%; thickener (0.05-0.5)%; adhesive (1-5)%; the balance is deionized water. The coating can provide uniform ion conduction while improving the uniform bonding between the diaphragm and the positive and negative electrodes, thereby further improving the cycle life of the high energy density battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano-level lithium battery diaphragm coating suitable for electro-hydraulic dynamics (EHD) jet printing technology. Background Art

[0002] Lithium batteries are modern batteries composed of positive electrodes, negative electrodes, separators and electrolytes. The electrolyte in the battery is mainly infiltrated in the battery separator. The lithium battery separator is an important functional material that separates the positive and negative electrodes of the battery and allows lithium ions to pass through. Another important function of the separator is to bond the positive and negative electrodes of the battery to the separator. How to achieve high performance, high energy density and high cycle life of lithium batteries is a key technical problem that needs to be solved in the development of modern lithium batteries. While developing new high-energy-density positive and negative electrode materials, it is also necessary to develop new separator coating technologies to meet the high-functionality requirements of battery cells. Coating adhesives on separator materials to strengthen the bonding between separators and electrodes and enhance the mechanical strength of the battery cells is an important solution to increase battery cycle times and battery life.

[0003] Modern high-end lithium batteries have partially adopted PVDF adhesive-coated diaphragm materials. There are two existing adhesive coating technologies on diaphragms; the first is full coverage coating, which uses a micro-concave roller or scraper to coat the adhesive emulsion on the surface of the porous PE diaphragm; the advantage of full coverage coating of the diaphragm is good adhesion but reduced conductivity. The second is rotary spraying, which can coat the adhesive emulsion on the diaphragm surface in the form of dots. The advantage of this technology is that the diaphragm has good conductivity, but the coating dots are irregular and amorphous, resulting in uneven diaphragm adhesion and conductivity distribution. Existing rotary spray slurry cannot be used in electro-hydraulic dynamics jet printing because of the mismatch of slurry conductivity and large particles, which will cause irregular spraying and severe nozzle clogging. Summary of the invention

[0004] Based on the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a nano-level lithium battery diaphragm coating suitable for electrohydrodynamic (EHD) jet printing technology, which can improve the uniform adhesion between the diaphragm and the positive and negative electrodes while also providing uniform ionic conductivity, thereby further improving the cycle life of high energy density batteries.

[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0006] The present invention provides a nanoscale lithium battery diaphragm coating suitable for electrohydraulic dynamics jet printing technology, comprising the following components in percentage by weight:

[0007]

[0008] As a further improvement of the present invention: the auxiliary agent is polymethyl methacrylate.

[0009] As a further improvement of the present invention: the emulsifier BYK-LPX 20990.

[0010] As a further improvement of the present invention: the thickener is sodium carboxymethyl cellulose CMC.

[0011] As a further improvement of the present invention: the binder is acrylic resin.

[0012] As a further improvement of the present invention: the molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer resin PVDF-HFP is 500,000-800,000, wherein the weight percentage of HFP in the copolymer is between 0.5% and 3%. Copolymer resins outside this range are difficult to meet the requirements of lithium-ion batteries for electrode peeling force and swelling coefficient.

[0013] As a further improvement of the present invention: the coating is prepared by directly adding the raw material group % into water to form a suspension emulsion, and then drying to form a powdered resin. The powdered resin contains polyvinylidene fluoride-hexafluoropropylene copolymer resin PVDF-HFP powdered particles, and its average particle size is between 2-10 microns.

[0014] As a further improvement of the present invention: the coating is prepared by adding a polyvinylidene fluoride-hexafluoropropylene copolymer resin PVDF-HFP suspension emulsion mixed with raw materials without drying treatment to other components to directly prepare an electro-liquid dynamic spray emulsion, wherein the emulsion particles are between 150-300 nanometers.

[0015] As a further improvement of the present invention: the lithium battery separator base film is a polyethylene porous base film for lithium batteries or a polyethylene porous base film coated with ceramics, the ceramics are coated on one side or both sides, the porosity of the separator is 40-60%, and the average pore size is 200-500 nanometers.

[0016] The stability of the emulsion is achieved by forming a stable suspension of particles in the liquid through the electrostatic repulsion of the particles (manifested in the Zeta potential). The addition of a thickener will increase the viscosity of the emulsion and at the same time increase the Zeta potential of the particles, thereby improving the stability of the emulsion at high voltage. Generally, high voltage will destroy the electrostatic repulsion between particles in the emulsion, causing the emulsion to break and cause the particles to agglomerate, thereby blocking the flow path. Existing emulsion technology cannot be applied to this high-voltage electro-hydraulic dynamics jet printing. The thickener can not only adjust the viscosity of the emulsion, but can also be used to adjust the conductivity of the emulsion so that the formula will not break under high voltage. However, the existing emulsion technology has poor stability under high voltage and is very easy to break, thereby causing flow path blockage.

[0017] In order to solve the shortcomings and deficiencies in the existing two types of membrane adhesive coating, the present invention proposes a slurry for electro-liquid dynamic jet printing, so that its conductive properties and the fluid physical properties of the emulsion meet the conditions of electro-liquid dynamic jetting, which can be used in electro-liquid dynamic jet printing to obtain a slurry formula for uniform dot coating, which can improve the uniform bonding between the membrane and the positive and negative electrodes while also providing uniform ion conductivity to further improve the cycle life of high energy density batteries. Another advantage is that the amount of binder can be saved, thereby reducing the production cost of the coated membrane. In addition, the suspended emulsion has good stability, the emulsion has a certain conductivity, good adhesion to the base film, appropriate viscosity and surface tension, and good wettability with the base film.

[0018] Another advantage of the coating of the present invention is that after the surface tension of the emulsion is adjusted by using ~5% emulsifier / hexanol conductive regulator), a circular ring-shaped mountain is formed on the surface of the diaphragm, thereby increasing the bonding effect between the diaphragm and the electrode, reducing the chance of separation of the diaphragm and the battery electrode, so as to achieve the effect of increasing the cycle life of the battery.

[0019] The industrial production of PVDF binder resin is made by emulsion polymerization, and then the emulsion is made into powder by post-processing, and finally the PVDF resin powder sold on the market is obtained. The existing PVDF coating slurry for preparing lithium battery diaphragm PVDF coating is made by redispersing PVDF powder. In the present invention, the PVDF product that can be directly used in emulsion suspension polymerization is directly added to other formula ingredients to prepare a nano-scale dispersed emulsion, which has higher stability and particle uniformity.

[0020] Because the size, position and coverage of the coating dots can be precisely controlled by using the emulsion formula of the present invention through electro-hydraulic dynamic spray coating, the PVDF-HFP content in the emulsion can be reduced to less than 5% to achieve the bonding effect of other existing coating emulsions with a PVDF content of 15%. The cost of coating the adhesive using this technology is relatively lower.

[0021] Spin coating Electrostatic spraying Emulsion PVDF content (%) 15% 5% Coverage (%) 21% 7% Pole peeling force (N / m) 4.39 6.41

[0022] In addition, compared with the problem of emulsion loss during the rotary spraying process, the emulsion formula of the present invention is used for electro-hydraulic dynamic spray coating, and there is basically no emulsion loss during the process, which can further reduce the production cost of lithium battery separator coating. The difficulty of the present invention is that it is difficult for traditional slurries to maintain system stability at high voltages, and it is easy to break the emulsion and cause flow path blockage, thereby affecting the coating effect. This solution innovatively uses the auxiliary agent polymethyl methacrylate, and methyl methacrylate and PVDF-HFP achieve a special combination in the aqueous dispersion, which has an unexpected effect and effectively improves the coating effect of electro-hydraulic dynamic jet printing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention provides an operation diagram for use of a nano-level lithium battery diaphragm coating suitable for electro-hydraulic jet printing technology.

[0024] Figure 2 The present invention provides a process flow chart for preparing a nano-level lithium battery diaphragm coating suitable for electro-hydraulic dynamics jet printing technology.

[0025] Figure 3-Figure 7 They are respectively the dot-shaped PVDF-HFP coated nanoscale lithium battery separators prepared by electrohydraulic jet printing technology in Examples 1-5 of the present invention.

[0026] Figure 8 This is the diaphragm prepared by spin spraying in Comparative Example 4. DETAILED DESCRIPTION

[0027] The following is a further and more detailed description of a nano-level lithium battery separator coating suitable for electro-hydraulic dynamics jet printing technology provided by the present invention through specific embodiments;

[0028] The preparation method for coating the lithium battery separator of the present invention is to use an electro-liquid dynamics spray device (such as Figure 1 As shown), the emulsion made with the formula is sprayed onto the surface of the diaphragm base film in a dotted shape, and the coated base film is subjected to hot air drying treatment, and then rolled and slit. By adjusting the DC voltage and the distance between the electrodes on the electro-liquid dynamics spraying device, the size of the dots and the dot coverage density can be accurately adjusted. The position and density of the dots can be accurately adjusted by the position of the nozzle and the moving speed of the base film. Because the coating formula of the existing PVDF emulsion cannot meet the conditions of electro-liquid dynamics spraying, that is, due to its conductivity and high-voltage stability, jet printing cannot be achieved. Therefore, the emulsion formula of the present invention is developed on the basis of the existing coating emulsion to meet the conditions of electro-liquid dynamics spraying such as the special conductivity and stability of the emulsion to achieve jet printing. Compared with the lithium battery diaphragms prepared by the coating technology of other existing lithium battery diaphragms PVDF binders, the battery diaphragms prepared by the formula of the present invention combined with the electro-liquid dynamics jet printing technology can achieve uniformly distributed and regular circular dots, functionally have uniform bonding properties and consistent lithium ion conductivity at all parts of the diaphragm surface, and can also provide better lithium ion permeability.

[0029] Electro-hydraulic dynamic injection is carried out through a high-voltage electric field. During this process, the general PVDF-HFP binder emulsion will demulsify under high pressure, and the suspended solid particles will agglomerate and precipitate at the nozzle, causing blockage and making injection impossible.

[0030] The formula of the present invention adds (0.05-5)% of auxiliary agent PMMA polymethyl methacrylate to the polymerized PVDF-HFP powder. The emulsion suspension prepared by the mixture and other auxiliary materials can make the emulsion suspension more stable and not demulsify, and avoid the situation of nozzle blockage caused by precipitation. In addition, it is unexpectedly found that the addition of PMMA and other auxiliary agents can make the emulsion of the formula more stable and not demulsify under high voltage, so that point-like injection can be achieved. The principle is that the electrostatic repulsion effect in the emulsion is stronger.

[0031] The following examples introduce a specific preparation method of a nano-scale lithium battery separator coating suitable for electro-hydrodynamic EHD jet printing technology provided by the present invention and its application in battery separator coating.

[0032] There are two methods for preparing the emulsion of the present invention:

[0033] The first method is to directly use the PVDF-HFP emulsion produced in the polymerization production process of PVDF and HFP as the main binder and then add other ingredients in the above formula to mix and form a stable emulsion suspension slurry.

[0034] The second method is to mechanically crush the powder particles formed by the polymerized and dried PVDF-HFP suspension emulsion to an average particle size of less than 1 micron, then add it to water, stir it at high speed and add other components in the formula to prepare a stable slurry; then use electro-liquid dynamics spraying to apply the binder slurry in a dotted manner on the surface of the PE diaphragm for lithium batteries, and the sprayed diaphragm is dried with hot air at 55 to 85 degrees Celsius. Such a coated diaphragm can be used to assemble lithium batteries.

[0035] The first method is implemented as follows:

[0036] The emulsion obtained after copolymerization reaction of PVFD-HFP has a molecular weight of 800,000. The product is synthesized in a laboratory. The solid content of the emulsion after synthesis is 15%, and the particle size of the emulsion is about 200 nanometers. (1-4%)wt% of an emulsifier BYK-LPX 20990 is added to the emulsion and dispersed evenly. Then (0.05-5)% of an auxiliary agent polymethyl methacrylate is added and dispersed by stirring. Then (1-5)% of an adhesive acrylic resin is added and stirred to be completely dissolved. Then (0.05-0.5)% of a thickener CMC is added, and then (0.5-8)% of a conductive regulator ethanol emulsion is added to complete the preparation.

[0037] Among them, BYK-LPX 20990 is a wetting and dispersing agent specially used for battery separator slurry. It is a structure of non-polar polydimethylsiloxane and hydrophilic polyether groups, which can significantly reduce the surface tension of the aqueous system.

[0038] The specific implementation of the second method is as follows:

[0039] The PVDF powder is LBG product of Arkema, with an average particle size of 6 to 7 microns. (5-20)% of the powder is added to water and stirred at high speed, then (1-4)% of the emulsifier BYK-LPX 20990 is added to the emulsion, then (0.05-5)% of the auxiliary agent polymethyl methacrylate is added, stirred and dispersed, then (1-5)% of the adhesive acrylic resin is added, stirred and completely dissolved, then (0.05-0.5)% of the thickener CMC is added, and then (0.5-8)% of the conductive regulator ethanol emulsion is added to complete the preparation.

[0040] A method for preparing a lithium battery diaphragm coated by electro-liquid dynamic jet printing using the formula of the present invention. The binder slurry is introduced into the spray head by a pump, and the spray head is used as the positive electrode. Under the power drive of the DC high-voltage electric field, the binder slurry is sprayed in dots on the PE lithium battery diaphragm placed on the negative plate. Usually, the surface of the PE diaphragm has been evenly coated with a layer of ceramic particles, such as the double-sided ceramic-coated PE diaphragm produced by Enjie Company. After the dot coating, the diaphragm quickly enters the hot air drying oven, which is composed of a multi-stage temperature drying section with a temperature ranging from 55°C to 85°C.

[0041] Before coating, the thickness of Enjie lithium battery separator is 12μm, the longitudinal tensile strength is 1500kgf / cm, the open porosity is 40%, the air permeability is 200sec / 100cc, the longitudinal shrinkage (105℃, 1) is <4%, and the transverse shrinkage (105℃, 1h) is 1.5%;

[0042] The main parameters of the coated diaphragm are: longitudinal tensile strength of 1500kgf / cm, open porosity of 40%, air permeability of 210sec / 100cc, longitudinal shrinkage (105℃, 1) of <4%, and transverse shrinkage (105℃, 1h) of 1.5%.

[0043] Example 1

[0044] 5% of Akema LBG PVDF-HFP powder particles and 1% of BYK LPX-20990 emulsifier were added to 93.4% of deionized water, stirred at 1000 rpm for 20 minutes, and then 0.05% of auxiliary agent polymethyl methacrylate was added and stirred for another 10 minutes.

[0045] Then add 1% acrylic resin (LG, Korea, acrylic resin BA122) as a binder, continue stirring until the binder is completely dissolved, and then add 0.05% thickener CMC (sodium carboxymethyl cellulose).

[0046] Then 0.5% conductivity regulator ethanol was added.

[0047] Then the electro-hydraulic dynamic jet printing coating can be carried out on the lithium battery separator. Single-sided coating is carried out on the base film.

[0048] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Single-sided dot coating is performed on the base film by electro-hydraulic power jet printing. The jet voltage is 5 kV. The jet flow rate is 0.3ul / min. The wet film after coating is dried by hot air. The coverage of the dot coating is 7% after coating, and the average diameter of the dot is 710 microns.

[0049] Example 2

[0050] 15% of Akema LBG PVDF-HFP powder particles and 4% of hydrophobin emulsifier were added to 62.5% of deionized water, stirred at 1000 rpm for 20 minutes, and then 5% of auxiliary agent polymethyl methacrylate was added, and stirring was continued for 10 minutes.

[0051] Then add 5% acrylic resin (LG, Korea, acrylic resin BA122) as a binder, continue stirring until the binder is completely dissolved, and then add 0.5% thickener CMC (sodium carboxymethyl cellulose).

[0052] Then 8% conductivity regulator ethanol was added.

[0053] Then the electro-hydraulic dynamic jet printing coating can be carried out on the lithium battery separator. Single-sided coating is carried out on the base film.

[0054] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Single-sided dot coating is performed on the base film by electro-liquid dynamic jet printing. The jet voltage is 5 kV. The jet flow rate is 0.3ul / min. The wet film after coating is dried by hot air. The coverage of the dot coating is 20% after coating, and the average diameter of the dot is 940 microns.

[0055] Example 3

[0056] 12% of Akema LBG PVDF-HFP powder particles and 2% of BYKLPX-20990 emulsifier were added to 77.3% of deionized water, stirred at 1000 rpm for 20 minutes, and then 0.3% of auxiliary agent polymethyl methacrylate was added and stirred for another 10 minutes.

[0057] Then add 3% acrylic resin (Korea LG, acrylic resin BA122) as a binder, continue stirring until the binder is completely dissolved, and then add 0.4% thickener CMC (sodium carboxymethyl cellulose).

[0058] Then 5% conductivity regulator ethanol was added.

[0059] Then the electro-hydraulic dynamic jet printing coating can be carried out on the lithium battery separator. Single-sided coating is carried out on the base film.

[0060] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Single-sided dot coating is performed on the base film by electro-hydraulic power jet printing. The jet voltage is 10 kV. The jet flow rate is 0.3ul / min. The wet film after coating is dried by hot air. The coverage of the dot coating is 18% after coating, and the average diameter of the dot is 510 microns.

[0061] Example 4

[0062] 15% of Akema LBG PVDF-HFP powder particles and 4% of BYKLPX-20990 emulsifier were added to 62.5% of deionized water, stirred at 1000 rpm for 20 minutes, and then 5% of auxiliary agent polymethyl methacrylate was added, and stirring was continued for 10 minutes.

[0063] Then add 5% acrylic resin (LG, Korea, acrylic resin BA122) as a binder, continue stirring until the binder is completely dissolved, and then add 0.5% thickener CMC (sodium carboxymethyl cellulose).

[0064] Then 8% conductivity regulator ethanol was added.

[0065] Then the electro-hydraulic dynamic jet printing coating can be carried out on the lithium battery separator. Single-sided coating is carried out on the base film.

[0066] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Single-sided dot coating is performed on the base film by electro-liquid dynamic jet printing. The jet voltage is 10 kV. The jet flow rate is 0.3ul / min. The wet film after coating is dried by hot air. The coverage of the dot coating is 21% after coating, and the average diameter of the dot is 530 microns.

[0067] Example 5

[0068] 2% BYK LPX-20990 emulsifier was added to a PVDF-HFP emulsion with a solid content of 15% prepared by polymerization reaction and containing 74.3% deionized water, and stirred at 1000 rpm for 20 minutes, and then 0.3% auxiliary agent polymethyl methacrylate was added and stirred for another 10 minutes.

[0069] Then add 3% acrylic resin (Korea LG, acrylic resin BA122) as a binder, continue stirring until the binder is completely dissolved, and then add 0.4% thickener CMC (sodium carboxymethyl cellulose).

[0070] Then 5% conductivity regulator ethanol was added.

[0071] Then the electro-hydraulic dynamic jet printing coating can be carried out on the lithium battery separator. Single-sided coating is carried out on the base film.

[0072] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Single-sided dot coating is performed on the base film by electro-hydraulic power jet printing. The jet voltage is 10 kV. The jet flow rate is 0.3ul / min. The wet film after coating is dried by hot air. The coverage of the dot coating is 19% after coating, and the average diameter of the dot is 500 microns.

[0073] Comparative Example 1

[0074] 5% of Akema LBG PVDF-HFP powder particles and 1% of BYK LPX-20990 emulsifier were added to 93% of deionized water and stirred at 1000 rpm for 20 minutes.

[0075] Then, 1% acrylic resin (LG, Korea, acrylic resin BA122) was added as a binder, and stirring was continued until the binder was completely dissolved.

[0076] Then, electro-hydraulic dynamic jet printing coating was performed on the lithium battery separator. Single-sided coating was performed on the base film.

[0077] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Electro-hydraulic power jet printing is used to perform single-sided dot coating on the base film. The jet voltage is 5 kV. The jet flow rate is 0.3ul / min. The jet cannot be sprayed normally, and the flow path is seriously blocked.

[0078] Comparative Example 2

[0079] 5% of Akema LBG PVDF-HFP powder particles and 1% of BYKLPX-20990 emulsifier were added to 93.95% of deionized water and stirred at 1000 rpm for 20 minutes.

[0080] Then add 1% acrylic resin (LG, Korea, acrylic resin BA122) as a binder, continue stirring until the binder is completely dissolved, and then add 0.05% thickener CMC (sodium carboxymethyl cellulose).

[0081] Then, electro-hydraulic dynamic jet printing coating was performed on the lithium battery separator. Single-sided coating was performed on the base film.

[0082] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Electro-hydraulic power jet printing is used to perform single-sided dot coating on the base film. The jet voltage is 5 kV. The jet flow rate is 0.3ul / min. It cannot be jetted normally, but the flow path is unobstructed.

[0083] Comparative Example 3

[0084] 5% of Akema LBG PVDF-HFP powder particles and 1% of BYK LPX-20990 emulsifier were added to 93.5% of deionized water and stirred at 1000 rpm for 20 minutes.

[0085] Then, 1% acrylic resin (LG, Korea, acrylic resin BA122) was added as a binder, and stirring was continued until the binder was completely dissolved.

[0086] Then 0.5% conductivity regulator ethanol was added.

[0087] Then, electro-hydraulic dynamic jet printing coating was performed on the lithium battery separator. Single-sided coating was performed on the base film.

[0088] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. Electro-hydraulic dynamic jet printing is used to perform single-sided dot coating on the base film. The jet voltage is 5 kV. The jet flow rate is 0.3ul / min. The jet can be sprayed normally at the beginning, but the flow path is soon blocked by the sediment after demulsification.

[0089] Comparative Example 4

[0090] 15% of Akema LBG PVDF-HFP powder particles and 1% of BYKLPX-20990 emulsifier were added to 83.95% of deionized water and stirred at 1000 rpm for 20 minutes.

[0091] Then add 1% acrylic resin (LG, Korea, acrylic resin BA122) as a binder, continue stirring until the binder is completely dissolved, and then add 0.05% thickener CMC (sodium carboxymethyl cellulose).

[0092] Then single-sided coating was performed on the base film using spin spraying on the lithium battery separator.

[0093] The base film is a polyethylene double-sided ceramic film (2+12+2 microns) produced by Shanghai Enjie Company. The wet film after coating is dried by hot air. The coverage of the dot coating after coating is 21%, and the average diameter of the dot is 1500 microns.

[0094] Diaphragm performance test

[0095] The air permeability and adhesion of the composite membranes obtained in Examples 1-5 and Comparative Examples 1-4 were tested. The specific test methods are as follows. The test results are shown in Table 1.

[0096] a. Breathability

[0097] The air permeability of the composite membrane was tested using a Gurley 4110 air permeability tester. The results are shown in Table 1.

[0098] b. Adhesion

[0099] Take a diaphragm with a complete membrane surface and no abnormal appearance, punch it into samples with a width of 25mm and a length of 100mm, take two punched diaphragm samples and stack them together, and press them on a hot press at a pressure of 3MPa and a temperature of 80℃ for 30min, and use a tensile tester to test the tensile force of the two bonded diaphragms, the tensile speed is 1m / min, and the bonding strength unit is N / m. The results are shown in Table 1.

[0100] Table 1:

[0101]

[0102] Note: Comparative Examples 1 to 3 have no test data because coating was not successfully performed.

[0103] It should be understood that the purpose of these embodiments is only to illustrate the present invention and is not intended to limit the protection scope of the present invention. In addition, it should also be understood that after reading the technical content of the present invention, those skilled in the art can make various changes, modifications and / or variations to the present invention, and all of these equivalent forms also fall within the protection scope defined by the appended claims of this application.

[0104] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.

Claims

1. Nanoscale lithium battery separator coating suitable for electrohydraulic dynamics jet printing technology, characterized in that The composition comprises the following components by weight percentage: The auxiliary agent is polymethyl methacrylate; The conductivity regulator is ethanol; The thickener is sodium carboxymethyl cellulose (CMC).

2. The nanoscale lithium battery separator coating suitable for electrohydraulic dynamics jet printing technology according to claim 1, characterized in that: The emulsifier is BYK-LPX 20990.

3. The nanoscale lithium battery separator coating suitable for electrohydraulic dynamics jet printing technology according to claim 1, characterized in that: The binder is acrylic resin.

4. The nanoscale lithium battery separator coating suitable for electrohydraulic dynamics jet printing technology according to claim 1, characterized in that: The molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer resin PVDF-HFP is 500,000-800,000, wherein the weight percentage of HFP in the copolymer is between 0.5% and 3%.

5. The nanoscale lithium battery separator coating suitable for electrohydraulic dynamics jet printing technology according to claim 1, characterized in that: The coating is prepared by directly adding raw material components into water to form a suspension emulsion, which is then dried to form a powdered resin. The powdered resin contains polyvinylidene fluoride-hexafluoropropylene copolymer resin PVDF-HFP powdered particles, and the average particle size thereof is between 2 and 10 microns.

6. The method for preparing a nanoscale lithium battery diaphragm coating suitable for electrohydraulic dynamics jet printing technology according to claim 1, characterized in that: The coating is prepared by directly adding other components to a suspended emulsion containing polyvinylidene fluoride-hexafluoropropylene copolymer resin PVDF-HFP, which is mixed with raw materials and not dried, to form an electro-liquid dynamics spray emulsion, wherein the emulsion particles are between 150-300 nanometers.

7. A lithium battery separator comprising the nanoscale lithium battery separator coating suitable for electrohydraulic dynamics jet printing technology according to any one of claims 1 to 5, characterized in that: The lithium battery separator base film is a polyethylene porous base film for lithium batteries or a polyethylene porous base film coated with ceramics. The ceramics are coated on one side or both sides. The porosity of the separator is 40-60% and the average pore size is 200-500 nanometers.

Citation Information

Patent Citations

  • Lithium ion battery diaphragm and preparation method thereof

    CN110571395A

  • Sprayed diaphragm for lithium ion battery and preparation method of sprayed diaphragm

    CN113363672A